The Chronology of the Revelation of the Verses of Surah Al-Baqarah - Al-Serhan, Moayyad Tehetoh; Shukri , Ahmad Khaled (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This study aims to establish an accurate or approximate timeline for the revelation of the verses of Surah Al-Baqarah, as such knowledge assists both the contemplator and the researcher in understanding the chronology of Qur’anic revelation. It also seeks to analyze the historical context of the surah’s revelation by examining the events that accompanied its descent in Madinah. Methods: The research induces and traces the verses of Surah Al-Baqarah and their revelation over the entire Madinan era; examines the narrations related to the causes of revelation (asbāb al-nuzūl); and compares differences among narrations and interpretations provided by classical exegetes regarding the timing of the verses’ revelation. Results: The study provides approximate dates for the revelation of several verses, facilitating future studies of similar nature. It demonstrates the feasibility of determining chronological groupings of the verses and distributes their revelation across the years of the Madinan period. Conclusion: The study emphasizes the importance of continuing efforts to trace the chronological order of Qur’anic verses, as this contributes significantly to thematic exegesis and enhances the field of Qur’anic revelation studies.